Digital transformation of organizations and their organizational cultures. A case study in a national defense industry - Kapotas, Spyridon (International Conference on Business and Economics - Hellenic Open University, 2023)
Digital transformation has become vital for organizations in order for them to differentiate from competitors providing a competitive advantage in the fast-changing environment they operate. Digital transformation is considered as a radical transformation affecting organization’s products, services, people and processes while improving performance. It is a risky and tremendous challenge for most organizations. Based on a dissertation with the current paper an approach on digital transformation, in a national defense company is attempted. Products and services provided are characterized through high quality standards and a strong culture. Those characteristics are considered a fruitable ground for providing a framework to transform an organization into a digital one. Taking into consideration the above, literature research on digital transformation of organizations and their benefits are provided. The digitalization process is analyzed in order to show the building blocks of transforming the organization into a digital one. However, in order to start such a process, the organization has to have an adaptive high performance organization culture. This is considered as the base to start the digitalization process. In order for the organization to have such a culture, current situation has to be assessed and certain actions to be taken. An assessment of above-mentioned company is presented and actions proposed. It is obvious that organizational digital transformation is inextricably linked with an organizational culture change. The benefits and barriers from such a transformation are shown and finally proposals presented regarding a digital strategy implementation as well as a vision and mission statement for the company. EL Classifications: M14. Key words: Digital transformation, digitalization process, digital strategy, organizational culture change, vision and mission statement